2013
DOI: 10.1242/bio.20135793
|View full text |Cite
|
Sign up to set email alerts
|

The cytosolic N-terminus of CD317/tetherin is a membrane microdomain exclusion motif

Abstract: SummaryThe integral membrane protein CD317/tetherin has been associated with a plethora of biological processes, including restriction of enveloped virus release, regulation of B cell growth, and organisation of membrane microdomains. CD317 possesses both a conventional transmembrane (TM) domain and a glycophosphatidylinositol (GPI) anchor. We confirm that the GPI anchor is essential for CD317 to associate with membrane microdomains, and that the TM domain of CD44 is unable to rescue proper microdomain associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Crosslinking of BST-2 by virion tethering or antibody binding can trigger activation of the NF-jB pathway as well as overexpression of BST-2 [23,24,34], presumably due to the resultant clustering of BST-2 in the lipid raft microdomains. Alternatively, it has been suggested these lipid raft microdomains themselves may act as signaling platforms, and the role of BST-2 in maintaining and organizing these rafts may therefore be indirectly responsible for signaling activity [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crosslinking of BST-2 by virion tethering or antibody binding can trigger activation of the NF-jB pathway as well as overexpression of BST-2 [23,24,34], presumably due to the resultant clustering of BST-2 in the lipid raft microdomains. Alternatively, it has been suggested these lipid raft microdomains themselves may act as signaling platforms, and the role of BST-2 in maintaining and organizing these rafts may therefore be indirectly responsible for signaling activity [20].…”
Section: Discussionmentioning
confidence: 99%
“…This apparent discrepancy raised the possibility that the observed effects of BST-2 were occurring via different pathways. Indeed, multiple functions have been ascribed to BST-2, including interaction with the cytoskeleton and organization of membrane microdomains [3,[19][20][21] as well as viral sensing and intracellular signaling [22][23][24][25]. Our investigation into how BST-2 may have inhibited influenza virus reverse genetics led us to the demonstration that BST-2 is capable of down-regulating transient protein expression and identification of a potential novel BST-2 antiviral mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Bsr GI digestion of pcDNA-Clover removed the initial stop codon of the fluorochrome coding sequence, thereby enabling the correct expression of the Clover-BST-2 fused protein. Since the membrane localization signal of BST-2 is determined by both the anchor signal located in the transmembrane domain and the GPI-anchor, addressing of the BST-2 fusion protein is not disrupted in those conditions [26,28]. …”
Section: Methodsmentioning
confidence: 99%
“…Viral particles are then susceptible to internalization into endosomal compartments and undergo subsequent degradation [17,18,23,24,25]. Structurally BST-2 is a type II integral membrane protein, with the N-terminus inside the cell cytoplasm, a single membrane spanning domain, and a C-terminus modified by the addition of an unusual GPI (glycosylphosphatidylinositol) anchor [26,27,28,29,30]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also suggested that the linkage of tetherin with the cortical actin network plays a role in the organization of lipid rafts (22,23). However, the mechanism of how the cortical actin network is involved in tetherin location and tetherin antiviral activity remains to be determined.…”
mentioning
confidence: 99%